Treatment of Migrant Workers: the Islamic Perspective - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig (INSI Publications, 2012)
It is heard of that migrant workers are sometimes abused by their employers, especially blue collared workers as they are mostly from underprivileged families who have left their countries to seek their fortune. Taking advantage of their upper hand, some employers compel them to work under terrible conditions, some are kept as slaves, unpaid and later disposed off, some are subject to deplorable living conditions, some women migrant workers are forced to ‘please’ their male employers to retain their jobs and some even forced into prostitution after entering a foreign land with the false hope of getting a respectable job. The Quran and the Sunnah of the Prophet Muhammad (SAW), had, for more than fourteen centuries ago, brought human rights to workers. In the context of employer and employee relationship, it is based on the concept of brotherhood and not that of superior and subservient. Employers should be considerate, just and kind towards their workers. Further, they should be forgiving and compassionate. This includes an employer’s duty to look after the comfort and well being of employees, to treat a worker as his brother and work assigned should commensurate to his capacity. Unfortunately, however, exploitation of migrant workers is still a recurring phenomenon across the globe including the Muslim world. Hence, it is worthwhile to reflect again the injunctions from the Quran and the Sunnah of the Prophet (SAW). This paper would therefore discuss the treatment of workers in the workplace from the Islamic perspective and further include an employee’s obligation to perform his work conscientiously and to be trustworthy, among others.